Thermal and Sound Insulation Properties of Organic Biocomposite Mixtures - Pop, Mihai Alin; Croitoru, Cătălin; Matei, Simona; Zaharia, Sebastian-Marian; Coșniță, Mihaela; Spîrchez, Cosmin (MDPI AG, 2024)
Sustainable building materials with excellent thermal stability and sound insulation are crucial for eco-friendly construction. This study investigates biocomposites made from cellulose pulp reinforced with beeswax, fir resin, and natural fillers like horsetail, rice flour, and fir needles. Eight formulations were obtained, and their thermal resistance, oxidation temperature, and acoustic properties were evaluated. Biocomposites exhibited significant improvements compared to conventional materials. Oxidation temperature onset increased by 60-70 degrees C compared to polyurethane foam or recycled textiles, reaching 280-290 degrees C. Sound absorption coefficients ranged from 0.15 to 0.78, with some formulations exceeding 0.5 across mid-frequencies, indicating good sound-dampening potential. These findings demonstrate the promise of these biocomposites for sustainable construction, offering a balance of thermal and acoustic performance alongside environmental and health benefits.
Keywords: thermal properties; sound insulation; biocomposites; paper pulp; internal architectures